(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The presence of Fish fauna and its economic importance in Bennetura reservoir from Osmanabad district(M.S.) India. The work was carried out during a year June 2021 to May 2022. Location of Bennetura reservoir 76°-27"-40", longitude and 17°- 47"- 40" latitude. It’s a manmade dam having a Maximum height of 13.38-meter catchment area is 79.58 sq. Kms and capacity of live storage 11.47mm3 full tank level water 10.30m. Its nine villages are in command and the dam is constructed in the year of1984. The Bennetura reservoir distance from the Omerga to the dam is about 18 Km. The water is used for irrigation, agriculture, sugar factory, domestic activity, drinking and fishery purpose. The result of the present investigation Reval the occurrence of 19 species belonging to the 06 orders 08 families. The member of the family Cyprinidae was dominant with 09 species to be followed by Channidae and Bagridae and Notopteridae represented by two species and the family Siluridae,clariidae, mastacemblidae and Cichlidae by single species and economic importance of fishes Occurance in Bennetura reservoir.